Healthcare-Associated Infections: Epidemiology, Diagnostics, and Management in Internal Medicine - Pricilla Putri Derlian Dohude; Novrina Situmorang (Jurnal Kedokteran Methodist, 2025)
Background: Nosocomial infections, particularly those occurring after 72 hours of patient admission, present a serious challenge in hospitals. These gram-negative bacteria, including Escherichia coli, Klebsiella pneumoniae, and Shigella, can lead to various infections such as urinary tract infections and nosocomial pneumonia. Nosocomial pneumonia, which encompasses Hospital-Acquired Pneumonia (HAP) and Ventilator- Associated Pneumonia (VAP), is associated with high mortality rates and can spread through contact transmission. The primary causes of these infections include prolonged hospitalization, severity of illness, and excessive use of antibiotics, which can enhance bacterial resistance. To prevent the spread of nosocomial infections, stringent hygiene practices and proper aseptic procedures are essential, along with prudent antibiotic management based on laboratory results. These preventive measures are crucial for improving the quality of healthcare services in hospitals and reducing the risk of nosocomial infections